The treatment of international sports organisations in Swiss national accounts - Camille Gonseth; Philippe Küttel (Eurostat Review on National Accounts and Macroeconomic Indicators (EURONA), 2022)
Switzerland is home to numerous international sports organisations and federations. They represent a major measurement challenge for statisticians in Switzerland because of their cyclical and increasingly important revenues generated by the staging of major sports events. By influencing Swiss GDP growth rates, they make official figures more difficult to interpret for domestic policy purposes. In Switzerland's decentralised statistical system, they also threatened to increase inconsistency between the national accounts and the balance of payments. To address this situation, the producers of these statistics worked together to provide a coordinated response to improve the quality and consistency of the data of these organisations in the different statistical domains and to provide new statistical information for short-term analyses. This work started in 2019 and is still ongoing. It has led to the establishment of a permanent working group between these institutions to discuss the treatment of international sports organisations and major sport events. In addition to monitoring their development, the next steps involve further deepening the understanding of their functioning and moving towards more international cooperation. The paper presents the economic model and examines the characteristics of the three most important organisations, namely FIFA, the IOC and UEFA. It then discusses the work carried out in the Swiss statistical system, which resulted in the implementation of a revised statistical treatment of their transactions in the benchmark revision of the Swiss national accounts in 2020. The paper concludes with a discussion of outstanding issues.
Keywords: E01; F55; F60; Z20; 330; national accounts; international sports organisations; major sports events; globalisation; intellectual property products